Rituximab maintenance improves outcomes of transformed diffuse large B-cell lymphoma: a retrospective study of 519 cases with de novo diffuse large B-cell lymphoma and 62 cases with concurrent diffuse large B-cell lymphoma and follicular lymphoma. Issue 9 (29th July 2021) - Uryu, Hideki; Mishima, Yuko; Tsuyama, Naoko; Yokoyama, Masahiro; Nishimura, Noriko; Fukuta, Takanori; Shirouchi, Yuko; Okabe, Takashi; Inoue, Norihito; Takeuchi, Kengo; Terui, Yasuhito
Abstract: Although outcomes of transformed diffuse large B-cell lymphoma (DLBCL) from follicular lymphoma (FL) were improved using rituximab-combined immunochemotherapy, the efficacy of subsequent rituximab maintenance (RM) remains unclear. We retrospectively analyzed the prognoses of 519 patients with de novo DLBCL and 62 patients with concurrent DLBCL and FL (concurrent-DLBCL/FL). Progression-free survival (PFS) was shorter in patients with concurrent-DLBCL/FL than in de novo DLBCL ( p =.030). Twenty-four patients with concurrent-DLBCL/FL received RM after induction therapy, and they achieved better OS and PFS ( p =.010 and p <.001, respectively) with lower risk of relapse ( p <.001) than the non-RM group. Moreover, concurrent-DLBCL/FL showed better subsequent OS and PFS after recurrence than de novo DLBCL ( p =.0083 and p =.0044, respectively). Our study indicates that in the face of a high relapse rate, concurrent-DLBCL/FL is manageable and benefits from RM.